2010
DOI: 10.1371/journal.pone.0013423
|View full text |Cite|
|
Sign up to set email alerts
|

Common Household Chemicals and the Allergy Risks in Pre-School Age Children

Abstract: BackgroundThe risk of indoor exposure to volatile organic compounds (VOCs) on allergic airway diseases in children remains unknown.ObjectiveWe examined the residential concentrations of VOCs, emitted from building materials, paints, furniture, and other lifestyle practices and the risks of multiple allergic diseases as well as the IgE-sensitization in pre-school age children in Sweden.MethodsIn a case-control investigation (198 case children with asthma and allergy and 202 healthy controls), air samples were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
103
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(107 citation statements)
references
References 40 publications
0
103
1
3
Order By: Relevance
“…In seven out of 9 cities the average TVOC level was higher than the Chinese Indoor Air Quality Standard (GB/T 18883-2002) [25] of 0.6 mg/m 3 as an 8-hour average. Finally, modern chemicals including phthalates [12], and glycol ethers [13] emitted by indoor decorations and furniture have shown a strong association with asthma and allergies. In this study, 28.7% of families reported new decoration before children's birth and 31.6% new furniture, with more than 60% (64.6%) of children living in the current place since children's birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In seven out of 9 cities the average TVOC level was higher than the Chinese Indoor Air Quality Standard (GB/T 18883-2002) [25] of 0.6 mg/m 3 as an 8-hour average. Finally, modern chemicals including phthalates [12], and glycol ethers [13] emitted by indoor decorations and furniture have shown a strong association with asthma and allergies. In this study, 28.7% of families reported new decoration before children's birth and 31.6% new furniture, with more than 60% (64.6%) of children living in the current place since children's birth.…”
Section: Resultsmentioning
confidence: 99%
“…Prenatal exposure and early life factors have been less thoroughly studied [6]. Till now, studies have reported that prenatal exposure to tobacco smoke [7,8], presence of home mold odor [9], early life presence of particle-board furniture [10], pollen or spores [11], and new chemicals [12,13] were associated with respiratory symptoms, including asthma and allergic rhinitis, in children later in life.…”
mentioning
confidence: 99%
“…However, even products we found to be non-cytotoxic may produce different, possibly stronger, effects when used repeatedly at full strength doses. As related examples, PG, which is "generally regarded as safe" and was non-cytotoxic for all cell types in the MTT assay, increased respiratory, throat and nasal symptoms, and cause vocal cord inflammation with prolonged inhalation by theater workers [24], and chronic exposure to PG in indoor air may induce or exacerbate allergic symptoms, asthma, and rhinitis [25].…”
Section: Discussionmentioning
confidence: 99%
“…People spend a large part of their time indoors and pre-school children spend a longer time in homes compared with adults [15,16]. The indoor environment, especially in homes, has been implicated as having an important role in inducing and/or exacerbating asthma and allergies among children [17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%